Analisis Faktor-faktor yang Mepengaruhi Penggunaan e filing Bagi Wajib Pajak Orang Pribadi (Studi Empiris pada Wajib Pajak di KPP Surakarta) - Mujiyati Mujiyati; Septarina Wahyuningtyas (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2019)
This study aims to determine the factors that influence the intensity ofthe behavior of taxpayers to use e-filing taxpayers, especiallyindividuals in the city of Surakarta. The variables used in this studyare the dependent variable, namely the intensity of the behavior oftaxpayers in using e-filing, while the independent variables used areperceived usefulness, simplicity, complexity, volunteerism,experience, security and confidentiality, and readiness of Informationtechnology taxpayers. The sample in this study is individualtaxpayers who report SPT using e-Filing in Surakarta.The sample collection method used in this study is conveniencesampling which was taken 100 samples. The data used in this studyare primary data using questionnaires. Data analysis in this studyuses the basic theory of Technology Acceptance Model (TAM) andthe SPSS program. The data analysis technique used is multiplelinear regression. The results of this study indicate that thesignificance at the level of 0.05 Perception, perceived ease ofUsability, complexity, Volunteerism, experience, security andconfidentiality, and readiness of taxpayer information technologysignificantly influence the intensity of behavior in using e-Filing